Diverse Religious Coalitions and Legislator Voting - Van Geest, Fred ca. 21. Jh. (The journal of religion & society, 2014)
Diverse religious coalitions have been found to be influential in shaping certain foreign policy legislation, but little research has examined the effect of religious coalitions on contemporary domestic legislation. This paper examines the extent to which a diverse religious coalition in Minnesota representing Catholics, Protestants, Jews, and Muslims, is more likely to have sway over legislators when they are united than when they are divided. Most members of the legislature claim a religious affiliation that is a part of the Joint Religious Legislative Coalition. This paper explores this question by examining twelve legislative votes between 2011 and 2013, including seven where a religious coalition takes a unified position and five where religious groups in the state are divided.